Distinct characteristics of Tregs of newborns of healthy and allergic mothers - Černý, Viktor; Hrdý, Jiří; Novotná, Olga; Petrásková, Petra; Boráková, Kristýna; Kolářová, Libuše; Prokešová, Ludmila (PloS one, 2018)
Allergic diseases represent a major issue in clinical and experimental immunology due to their high and increasing incidence worldwide. Allergy status of the mother remains the best predictor of an individual's increased risk of allergy development. Dysregulation of the balance between different branches of immune response, chiefly excessive polarization towards Th2, is the underlying cause of allergic diseases. Regulatory T cells (Tregs) play a pivotal role in the timely establishment of physiological immune polarization and are crucial for control of allergy. In our study we used flow cytometry to assess Tregs in cord blood of newborns of healthy (n = 121) and allergic (n = 108) mothers. We observed a higher percentage of Tregs (CD4+CD25+CD127lowFoxP3+) in cord blood of children of allergic mothers. However, the percentage of cells expressing extracellular (PD-1, CTLA-4, GITR) and intracellular (IL-10, TGF-β) markers of function was lower (significantly for PD-1 and IL-10) within Tregs of these children. Furthermore, Helios- induced Tregs in the cord blood of children of allergic mothers were decreased. These results were supported by a decrease in plasma levels of IL-10 and TGF-β in cord blood of newborns of allergic mothers, implying lower tolerogenic capacity on the systemic level. Taken together, these findings reflect deficient function of Tregs in the group with higher risk of allergy development. This may be caused by a lower maturation status of the immune system, specifically Tregs, at birth. Such immaturity may represent an important mechanism involved in the increased risk of allergy in children of allergic mothers.
Keywords: fetální krev; lidé; T-Lymphocytes, Regulatory; matky; náchylnost k nemoci; Mothers; Female; cytokiny; regulační T-lymfocyty; Humans; Infant, Newborn; Risk; imunoglobulin E; Cytokines; alergie; riziko; novorozenec; ženské pohlaví; Disease Susceptibility; Hypersensitivity; Immunoglobulin E; Fetal Blood